2009
DOI: 10.1016/j.intcom.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Of pages and paddles: Children’s expectations and mistaken interactions with physical–digital tools

Abstract: An assumption behind new interface approaches that employ physical means of interaction is that these can leverage users' prior knowledge from the real world, making them intuitive or 'natural' to use. This paper presents a user study of tangible augmented reality, which shows that physical input tools can invite a wide variety of interaction behaviours and raise unmatched expectations about how to interact. Children played with interactive sequences in an augmented book using physical paddles to control the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 18 publications
(25 reference statements)
1
29
0
2
Order By: Relevance
“…Several frameworks [25][26][27] have already been proposed to study the design space of tangible interfaces [28,29]. For example, Hornecker and Dünser [30] showed that pupils expect the system to match the physical properties of the tangible interface.…”
Section: Paper-based Interfaces In Educationmentioning
confidence: 99%
“…Several frameworks [25][26][27] have already been proposed to study the design space of tangible interfaces [28,29]. For example, Hornecker and Dünser [30] showed that pupils expect the system to match the physical properties of the tangible interface.…”
Section: Paper-based Interfaces In Educationmentioning
confidence: 99%
“…Players engaging with this hybrid reality hold intuitive expectations that it will function like the real world [56]. They naturally assume that physical properties, such as gravity, collisions and spatial containment, will hold true in the hybrid environment.…”
Section: World Consistencymentioning
confidence: 99%
“…However, preliminary results from some recent studies indicate that there are features and affordances of AR -as exemplified by augmented storybooks -that might considerably hamper the user experience and, as a corollary, present obstacles to learning. For instance, studies by Hornecker & Dünser (Dünser & Hornecker, 2007;Hornecker, 2007;Hornecker & Dünser, 2009) of children interacting with augmented storybooks showed that the physical affordances of tangible input devices made children expect the AR objects to obey to and yield the same physical behaviour as in real life.…”
Section: Tangibility and Haptics In Digital Technologiesmentioning
confidence: 99%